CYBERSECURITY IN THE DIGITAL AGE - Xalilova Zarnigor Muhammadjon qizi; Ibrohimov Zikiriyo Muzaffar o‘g‘li (TADQIQOTLAR, 2025)
Abstract: In the digital age, cybersecurity plays a crucial role in protecting information, systems, and users from cyber threats. With the rapid expansion of digital technologies, online platforms, and smart devices, the risk of cyberattacks has significantly increased. This article examines the main challenges and forms of cyber threats, including malware, phishing, data breaches, and identity theft. It also highlights modern cybersecurity solutions such as encryption, multi-factor authentication, firewalls, and user awareness training. The study emphasizes the importance of building a secure digital environment and the need for continuous technological improvement and education to ensure information safety.